A literatura infantil no ensino-aprendizagem de alunos com transtorno do espectro autista - MOURA, Jacyara do Socorro de Campos (2021)
The influx of people with disabilities into mainstream schools is growing, thanks to the inclusion processes that have made these environments restructured and adapted to accommodate student diversity, including people with Autistic Spectrum Disorder, which is increasingly prevalent. Therefore, it is necessary to discuss methodologies for successful classroom entry. This paper aims to demonstrate how children's literature is relevant in the teaching-learning of students with Autistic Spectrum Disorder. This is an exploratory case study, conducted through bibliographical and qualitative studies, at Aldenora Ribeiro Araújo Nursery, in the city of Abaetetuba-Pará. The study establishes the importance of storytelling, the exploration of literatures in a delightful or directed way and the importance of the cultural and social environment for the person with ASD. Through the routine of activities that included daily reading and children's literature, it was possible to analyze the development of the target student affected by the disorder and his remarkable development of socialization and orality, which was his most impaired area. Children's literature then stands out as a facilitator in the teaching-learning process of autistic students in order to develop cognitive processes in the affected areas, stimulating knowledge and providing greater interaction of the individual with the world.